Python GUI programming cookbook: over 80 object-oriented recipes to help you create mindblowing GUIs in Python - Meier, Burkhard A (Quick Answers to Common Problems, 2015)
About This BookLearn efficient C++ network programming with minimum coding using Boost.AsioYour one-stop destination to everything related to the Boost.Asio libraryExplore the fundamentals of networking to choose designs with more examples, and learn the basics of Boost.AsioWho This Book Is ForThis book is for C++ network programmers with basic knowledge of network programming, but no knowledge of how to use Boost.Asio for network programming.